Τreatment and prevention of canine heartworm disease (dirofilariosis): what is new? - SINANIS (Θ.Ν. ΣΙNΑΝΗΣ) T. N.; KOUTINAS (Χ.Κ. ΚΟΥΤΙΝΑΣ) C. K. (Journal of the Hellenic Veterinary Medical Society, 2017)
Canine heartworm disease (dirofilariosis) is a frequent parasitic disease in Greece and other para-Mediterranean countries. Immediate adulticide therapy, followed by administration of microfilaricidals, has been the mainstay of heartworm treatment. However, a more recent approach has included the requirement to killing microfilariae and Wolbachia pipientis prior to adulticide treatment. Administration of prophylactic doses of milbemycin, moxidectin, ivermectin or selamectin for 2 to 3 months, as well as of doxycycline (10 mg kg-1 bw, per os, twice daily) for a month, seems to negate the ‘susceptibility gap’ and to decrease the possibility of pulmonary thromboembolism. Moreover, an alternative protocol of adulticide therapy (2.5 mg kg-1 bw of melarsomine, intramuscularly, followed by two further injections, 24-hours apart, a month later) is considered superior to the classical one, regardless of the clinical stage of the disease. Treatment of potential complications (right heart failure or vena cava syndrome) includes administration of heart failure medication and surgical removal of adult worms. Strict exercise restriction seems to play the most important role in reducing the possibility of pulmonary thromboembolism. Alternative protocol melarsomine administration, after treatment with macrocyclic lactones and doxycycline, increases the therapeutic effect and improves prognosis in earlier stages of the disease. Continuous (or at least during the warm period of the year) preventive administration of microfilaricidals coupled with annual serological testing of animals is important for effective disease control.